The effectiveness of computerized clinical guidelines in the process of care: a systematic review - Gianfranco Damiani; Luigi Pinnarelli; Simona C Colosimo; Roberta Almiento; Lorella Sicuro; Rocco Galasso; Lorenzo Sommella; Walter Ricciardi (2010)
Clinical practice guidelines have been developed aiming to improve the quality of care. The implementation of the computerized clinical guidelines (CCG) has been supported by the development of computerized clinical decision support systems.This systematic review assesses the impact of CCG on the process of care compared with non-computerized clinical guidelines.